Personal Binocular Vision Calibration Using Layered Random Dot Stereogram - Kim, Sung-Kyu; Kang, Min-Koo (2016 ASIA-PACIFIC SIGNAL AND INFORMATION PROCESSING ASSOCIATION ANNUAL SUMMIT AND CONFERENCE (APSIPA), 2016)
Visual discomfort (VD) is inevitable as long as stereoscopy is used in 3D displays, and there's a trade-off between depth impression and visual comfort. For this reason, technologies that control depth impression considering VD perception have attracted great interest of researchers. However, VD perception significantly varies according to various personal-factors as well as environmental factors, and evaluating VD perception still takes a lot of time and effort for viewing tests. We propose a simple and reliable method that calibrates stereo acuities, binocular fusion limits, and preferences for depth perception of individuals. For the experiment, four non-expert viewers attended, and the same viewing conditions were given to them. The experimental result confirmed that calibrated features in human binocular vision coincide with the literature except for slight variations among the attendees. The proposed method would be utilized across the whole 3D video technology chain from video capture to the display.